Potential use of fresh mulch to curb potato late blight epidemics in Brazil - Nazareno,Nilceu Ricetti Xavier de (2020)
ABSTRACT Field experiments were conducted during spring 2014 and fall and spring 2015 to determine the effect of fresh mulch on the development of Phytophthora infestans epidemics, in Lapa Municipality, Parana State, southern Brazil. The used cultivars were ‘Agata’, susceptible, and ‘BRS Ana’, moderately susceptible. The main treatment consisted in manually applying a 10cm-thick layer of fresh mulch when potato sprouts were emerging. Fresh mulch was prepared with plants available at that time of the year. For the spring experiments, fresh mulch was a mixture of oats, rye grass and wild radish (60 t/ha) and for the fall experiment, semi-ripe elephant grass (90 t/ha). Plots consisted of six 10m-long rows, spaced at 0.8m, containing 28 plants per row. Experimental design was in completely randomized blocks with four replicates. Natural inoculum was adopted. Percentage of leaf area was weekly estimated until the end of the plant cycle and the area under the disease progress curve (AUDPC) was calculated. Application of fresh mulch significantly reduced AUDPC by 32.1%, 12.4% and 23.1%, compared to control in all seasons, for ‘BRS Ana’ and by 26.1%, 2.8% and 12.0% for ‘Agata’. Application of fresh mulch showed to be a promising practice for the integrated management of late blight and for the protection of yields, especially in periods more favorable to the development of the disease. More detailed studies should be conducted on the plant type and amount of fresh mulch to be used, as well as on the possibility of reducing concentrations or increasing intervals between fungicide sprays.